Collaborative professional learning in inclusive education: a systematic literature review of implications and challenges - Nursyahida Sikri,; Nor Hasimah Ismail,; Siti Noor Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2025)
This systematic literature review (SLR) examines the role of Collaborative Professional Learning (CPL) in enhancing teacher effectiveness and fostering inclusive educational practices. With increasing emphasis on equity, inclusion, and continuous professional development in 21st-century education, CPL has emerged as a strategic model grounded in peer collaboration, reflective inquiry, and community-based learning. Following the PRISMA guidelines, a total of 87 records were initially identified through database searches across Google Scholar, Scopus, and Web of Science. After screening and eligibility assessment, 13 empirical studies published between 2010 and 2025 were included for full review. Thematic analysis was conducted to extract key patterns, focusing on four domains: instructional improvement, inclusive pedagogy, leadership and support, and enabling conditions for effective CPL implementation. The synthesis revealed strong convergence across studies regarding CPL’s impact on instructional quality, teacher confidence, and pedagogical adaptability. CPL was also found to promote culturally responsive teaching and differentiated strategies, especially when embedded within Universal Design for Learning (UDL) frameworks. Critical enablers included trust, distributed leadership, and sustained participation, while barriers such as time constraints, digital inequity, and fragmented policy environments hindered implementation, particularly in under-resourced contexts. CPL offers a viable and scalable approach to professional growth and inclusive practice when supported by systemic leadership, equitable policy, and collaborative school cultures. Future research should explore the long-term impact of digital and hybrid CPL models, particularly in rural and low-resource educational settings.